Effects of Deoxycholylglycine, a Conjugated Secondary Bile Acid, on Myogenic Tone and Agonist-Induced Contraction in Rat Resistance Arteries - Khurana, Sandeep (Public Library of Science, 2012)
BACKGROUND: Bile acids (BAs) regulate cardiovascular function via diverse mechanisms. Although in both health and disease serum glycine-conjugated BAs are more abundant than taurine-conjugated BAs, their effects on myogenic tone (MT), a key determinant of systemic vascular resistance (SVR), have not been examined. METHODOLOGY/PRINCIPAL FINDINGS: Fourth-order mesenteric arteries (170–250 µm) isolated from Sprague-Dawley rats were pressurized at 70 mmHg and allowed to develop spontaneous constriction, i.e., MT. Deoxycholylglycine (DCG; 0.1–100 µM), a glycine-conjugated major secondary BA, induced reversible, concentration-dependent reduction of MT that was similar in endothelium-intact and -denuded arteries. DCG reduced the myogenic response to stepwise increase in pressure (20 to 100 mmHg). Neither atropine nor the combination of L-NAME (a NOS inhibitor) plus indomethacin altered DCG-mediated reduction of MT. K(+) channel blockade with glibenclamide (K(ATP)), 4-aminopyradine (K(V)), BaCl(2) (K(IR)) or tetraethylammonium (TEA, K(Ca)) were also ineffective. In Fluo-2-loaded arteries, DCG markedly reduced vascular smooth muscle cell (VSM) Ca(2+) fluorescence (∼50%). In arteries incubated with DCG, physiological salt solution (PSS) with high Ca(2+) (4 mM) restored myogenic response. DCG reduced vascular tone and VSM cytoplasmic Ca(2+) responses (∼50%) of phenylephrine (PE)- and Ang II-treated arteries, but did not affect KCl-induced vasoconstriction. CONCLUSION: In rat mesenteric resistance arteries DCG reduces pressure- and agonist-induced vasoconstriction and VSM cytoplasmic Ca(2+) responses, independent of muscarinic receptor, NO or K(+) channel activation. We conclude that BAs alter vasomotor responses, an effect favoring reduced SVR. These findings are likely pertinent to vascular dysfunction in cirrhosis and other conditions associated with elevated serum BAs.